If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6+w=-28
We simplify the equation to the form, which is simple to understand
-6+w=-28
We move all terms containing w to the left and all other terms to the right.
+1w=-28+6
We simplify left and right side of the equation.
+1w=-22
We divide both sides of the equation by 1 to get w.
w=-22
| -3.5+2x=-13.5 | | 13x-(5x-11)=13 | | n/7.2+4.5=6.4 | | x+.0805x=924 | | x/-2=5.8 | | 3(5x+7)-2(5x-4)= | | x^2-8kx=14 | | c/4=101/2 | | t/0.5=26 | | n/10=-361/5 | | 15=h-7 | | 8[3+8(36)]= | | b+19=48 | | 16x=320 | | a/-0.7=-8 | | 72=6n | | h/-1=-4.7 | | 2-3t=-1/3(5-t)+1 | | e/-1=12.5 | | 10(0.1d-0.3)=0.2(d+21) | | d/20=-1/5 | | (5x+4)(5x-1)= | | c/8=-36 | | -(x+8)=2(ax+5) | | 0=x-men | | (X^4/y^2)^3 | | -27x-48= | | b/-3=41 | | (X^2/3)^2 | | a/9=-8 | | -79-83= | | 2/x+3=11 |